Kebijakan Angsuran Pajak Penghasilan Wajib Pajak Orang Pribadi Pengusaha Tertentu: Studi Kasus Usaha Mikro di Indonesia - Inasius, Fany (Bina Nusantara University, 2014)
The instalment of Income Tax for Individual Taxpayers of particular enterpreneur is determined at 0.75% of the total circulation of business under section 25 Income Tax Act, 2008. The prepaidâs payment of income tax implies the underpayment or overpayment of tax at the end of the tax year. If there is an overpayment of tax audits, it will be conducted according to the Law Number 28 of 2007 on the General Provisions of Taxation. This paper focuses on the discussion of income tax installments by individual taxpayer particular enterpreneur categorized as micro entrepreneurs. Based on the research conducted by the method of comparative research, descriptive and analytical documents, results show that the maximum limit of circulation to all types of businesses at the lowest rates and the type of agricultural businesses in the highest rates occur overpayment. It means the cost of taxation for individual taxpayers of particular entrepreneurs in micro business. This causes a particular burden for micro individual taxpayers of particular enterpreneur besides less aligned with the goal of the Income Tax Act change.